Strategi Pengelolaan Sampah Menggunakan Analisis SWOT : Studi Kasus TPA Regional Payakumbuh - Viandry Tetriva Putri; Slamet Raharjo; Rizki Aziz (Fakultas Teknik, 2023)
Overcapacity experienced by the Payakumbuh Regional Final Processing Site (TPA) caused landslides in 2017 so several rice fields and agricultural land around were buried. This TPA serves waste for four Regencies/Cities with a volume capacity of 400,000 m³. Every day there are approximately 200 tons of waste coming in from Payakumbuh, Limapuluh Kota, Bukittinggi, and Agam. Now the TPA's storage capacity is only around 130,540 m³. With landslides and almost full landfills, this proves that waste management at the TPA is not optimal. The aim of this study was to examine the waste management strategy at the Regional TPA of Payakumbuh using a qualitative approach using the SWOT Analysis (Strengths, Weakness, Opportunities and Threats) method. The research begins with measuring the composition of waste, interviewing the role of scavengers, and identifying internal-external factors in the SWOT analysis. Measurement results for the composition of organic waste are 81.24% and 18.76% inorganic waste, potential for recycled waste is 69.05% in the form of compost and 2.40% for saleable. The results showed that landfill facilities functioned well except for sorting sites, while the role of scavengers was very useful in reducing inorganic waste by 3 tons/day. And results of SWOT analysis are in quadrant I with 3 strategies produced, including increasing composting facilities at TPA, implementing policies for TPA users and increasing empowerment of scavengers at TPA.